Educational Needs Assessment of Spiritual Care in Nurses in Iran in 2021: Using Delphi Technique - Ashraf KHoramirad; zahra abedini; hoda ahmaritehran; Zohreh Khalajinia; Sarolah Shojaei; akram heidari; Sadegh Yousefi (Health, Spirituality and Medical Ethics, 2021)
Background and Objectives: Nurses are professionally and ethically obliged to provide spiritual care as part of comprehensive care for patients. The present study was conducted to determine the educational needs of nurses to provide spiritual care. Methods: This study was performed descriptively using the Delphi technique from September 2020 to April 2021 at Qom University of Medical Sciences. In the first stage, 10 specialists were selected by purposive sampling method and answered an open-ended question to determine the educational needs of spiritual care. After collecting opinions in three rounds, the needs with an agreement coefficient of more than 51% were prepared in the form of a 15-item questionnaire and the importance of the items was determined by 144 nurses. Needs with scores of 3 or higher were finalized and general and behavioral goals were set for them. Results: In the first, second, and third rounds, 47, 25, and 15 educational needs were determined, respectively, and five general objectives, including familiarity with the holistic approach to human beings and dimensions of health, familiarity with the concepts of spiritual care, familiarity with how obtaining a spiritual history, familiarity with the types of diagnoses and spiritual interventions, and familiarity with the principles of communication in spiritual care were determined. Conclusion: The results of the study can be used for developing a spiritual curriculum and a practical guide to providing spiritual care for nurses and other groups of the health team.